Tricuspid Regurgitation in Left Ventricular Systolic Dysfunction: Marker or Target? - Margonato, Davide; Ancona, Francesco; Ingallina, Giacomo; Melillo, Francesco; Stella, Stefano; Biondi, Federico; Boccellino, Antonio; Godino, Cosmo; Margonato, Alberto; Agricola, Eustachio (Frontiers in Cardiovascular Medicine, 2021)
Far from being historically considered a primary healthcare problem, tricuspid regurgitation (TR) has recently gained much attention from the scientific community. In fact, in the last years, robust evidence has emerged regarding the epidemiological impact of TR, whose prevalence seems to be similar to that of other valvulopathies, such as aortic stenosis, with an estimated up to 4% of people >75 years affected by at least moderate TR in the United States, and up to 23% among patients suffering from heart failure with reduced ejection fraction. This recurrent coexistence of left ventricular systolic dysfunction (LVSD) and TR is not surprising, considered the multiple etiologies of tricuspid valve disease. TR can complicate heart failure mostly as a functional disease, because of pulmonary hypertension (PH), subsequent to elevated left ventricular end-diastolic pressure, leading to right ventricular dilatation and valve tethering. Moreover, the so-called “functional isolated” TR can occur, in the absence of PH, as a result of right atrial dilatation associated with atrial fibrillation, a common finding in patients with LVSD. Finally, TR can result as a iatrogenic consequence of transvalvular lead insertion, another frequent scenario in this cohort of patients. Nonetheless, despite the significant coincidence of these two conditions, their mutual relation and the independent prognostic role of TR is still a matter of debate. Whether significant TR is just a marker for advanced left-heart disease, or a crucial potential therapeutical target, remains unclear. Aim of the authors in this review is to present an update concerning the epidemiological features and the clinical burden of TR in the context of LVSD, its prognostic value, and the potential benefit for early tricuspid intervention in patients affected by contemporary TR and LVSD.